Mosque-Based Community Empowerment in Improving the Economy of the Muhammadiyah Taqwa Mosque Dolok Masihul, Serdang Bedagai Regency - Hasibuan, Burju Amar Ma'ruf; Muniruddin, Muniruddin (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
In the context of community development, mosques can be used as a means to improve the welfare of worshippers through various forms of empowerment. This study aims to analyze the economic empowerment strategy of the congregation implemented by the Muhammadiyah Taqwa Mosque located in Dolok Masihul District, Serdang Bedagai Regency. The method used was qualitative descriptive, with data collection carried out through observation, in-depth interviews, and documentation studies. The findings of the study indicate that mosques play a role not only as a place of worship, but also as a center for economic empowerment of the ummah through various programs such as sharia-based cooperatives, skills training, and management of ummah funds. This empowerment has a positive impact on improving the economic welfare of pilgrims, building independence, and strengthening social solidarity. The active role of mosque administrators, collaboration with community leaders, and congregational participation are key factors for the success of the implementation of these programs.